2021
DOI: 10.1186/s12889-021-10355-1
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral profile, lifestyle and social skills in Portuguese adolescents

Abstract: Background Seventy percent of premature deaths in adults are due to behaviors initiated during adolescence. Therefore, it is essential to promote individual and social behaviors that educate adolescents in the ability to make healthy choices. Accordingly, the main goals of this study were to characterize Lifestyles and Social Skills, as well as identify homogeneous subgroups, in a sample of Portuguese adolescents. Methods A cross-sectional study wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
1
0
3
Order By: Relevance
“…However, the arithmetic means at baseline of 0.56 increased to 0.64 at the end-line. This finding aligns with the results of Magalhaes et al ( 9 ) from Portuguese, where 50.7% of adolescents exposed to a school-linked life skills intervention program demonstrated improved social skills. Similarly, in Spain, Gasol et al ( 10 ) reported a rate of 48%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the arithmetic means at baseline of 0.56 increased to 0.64 at the end-line. This finding aligns with the results of Magalhaes et al ( 9 ) from Portuguese, where 50.7% of adolescents exposed to a school-linked life skills intervention program demonstrated improved social skills. Similarly, in Spain, Gasol et al ( 10 ) reported a rate of 48%.…”
Section: Discussionsupporting
confidence: 91%
“…A study in India showed that 91.5–95.1% of participants improved their awareness of various life skill domains ( 1 , 7 , 8 ). Magalhães et al ( 9 ) and Gasol et al ( 10 ) stated that 50.7% Portuguese and 48% Spanish adolescents who were exposed to life skills training had reported practicing the newly learned social skills. Similarly, Pradeep et al ( 1 ) found that 91.6% of students in India reported improved awareness of life skills after participating in life skills training.…”
Section: Introductionmentioning
confidence: 99%
“…Este programa educativo ha demostrado efecto altamente significativo en las habilidades sociales según dimensiones de asertividad, comunicación, y toma de decisiones y significativa en la dimensión autoestima. Es fundamental promover comportamientos individuales y sociales que favorezcan la educación en los adolescentes y fortalezcan las Huyhua-Gutierrez, Sonia Celedonia; Díaz-Manchay, Rosa Jeuna; Luján-Espinoza, María Nelly y Tejada-Muñoz, Sonia Habilidades sociales en adolescentes desde la enseñanza virtual: Programa educativo de fortalecimiento en Amazonas-Perú________________________________________________ 446 Licencia de Creative Commons Atribución 4.0 Internacional (CC BY 4.0) https://creativecommons.org/licenses/by/4.0/deed.es capacidades que les permitan tomar decisiones saludables y se constituyan en personas de bien para la sociedad (Magalhães et al, 2021;Mendivil et al, 2023).…”
Section: Tabla 4 Efectividad Del Programa Educativo En El Fortalecimi...unclassified
“…Variables relacionadas con las habilidades sociales y creatividad en la adolescencia buenas puntuaciones en inteligencia emocional (Salavera et al, 2019;Trigueros et al, 2020), resiliencia (Jacome-Olacua et al, 2020Ruvalcaba Romero et al, 2019;Sifuentes-Gomez et al, 2020), autoconcepto (Tacca Huamán et al, 2020, potencia los comportamientos prosociales (Tesema et al, 2020) y, con ello, la calidad de vida (Lemonia et al, 2017;Romero-Oliva et al, 2017); este nivel alto de habilidades sociales también se relaciona con llevar un estilo de vida saludable basado en unos buenos hábitos de alimentación y la realización de ejercicio físico (Akelaitis y Lisinskiene, 2018;Magalhães et al, 2021;Nesi de Mello et al, 2019). Sin embargo, los adolescentes con carencias en habilidades sociales pueden verse afectados por problemas de salud mental (Nyarko et al, 2020), el abuso de sustancias o videojuegos (Pozveh y Saleh, 2020; Zegarra y Cuba, 2017), riesgo de suicidio (Gonzáles et al, 2019;Salavera et al, 2019), problemas de sobrepeso (Aydos y Akyol, 2018) o la tendencia a emplear conductas disruptivas como es el acoso hacia sus iguales (Andrade Mendoza González y Maldonado Ramírez, 2017;Trigueros et al, 2020).…”
Section: A González Moreno Y MM Molero Juradounclassified